1976
DOI: 10.1152/jappl.1976.40.3.425
|View full text |Cite
|
Sign up to set email alerts
|

A square-pulse flow method for measuring characteristics of the arterial bed

Abstract: A device was designed to provide a "square" pulse of blood flow into the arterial system. Pulses were injected into the carotid artery of the rabbit during transient cardiac arrest. Analysis of pressure response curves generated by the flow provides information as to the state of the arterial tree. With certain assumptions it is possible to estimate from these curves lumped values of peripheral resistance, critical closing pressure, and arterial compliance. In a series of 12 rabbits the mean value of periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A total of 1255 unique publications were identified after removal of duplicates; 1235 were excluded during screening. The remaining 20 studies 4851,5469 with P zf data were included in a meta-analysis (Figure 3); these included data from dog, rat, pig and human; eight of these articles also provided data on MCFP from the same studies. Some further details of these studies are shown in Supplementary Table S1.…”
Section: The Relation Of Pzf To P∞ and The Physiological Interpretatimentioning
confidence: 99%
“…A total of 1255 unique publications were identified after removal of duplicates; 1235 were excluded during screening. The remaining 20 studies 4851,5469 with P zf data were included in a meta-analysis (Figure 3); these included data from dog, rat, pig and human; eight of these articles also provided data on MCFP from the same studies. Some further details of these studies are shown in Supplementary Table S1.…”
Section: The Relation Of Pzf To P∞ and The Physiological Interpretatimentioning
confidence: 99%
“…Data are shown as means (95% confidence intervals).A total of 1255 unique publications were identified after removal of duplicates; 1235were excluded during screening. The remaining 20 studies(48)(49)(50)(51)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69) with Pzf data were included in a meta-analysis (Figure 2); these included data from dog, rat, pig and human; 8 of these articles also provided data on MCFP from the same studies. Some further details of these studies are shown inSupplementary Table S1.From this analysis Pzf = 26.5 (23.4, 29.5) mmHg (Figure 3; 20 studies; mean (95% confidence interval); n = 311; I 2 = 97%; P <0.001) and MCFP = 10.6 (9.3, 12.0) mmHg (8 studies; n = 178; I 2 = 96%; p < 0.001).…”
mentioning
confidence: 99%